Necrotizing cholecystitis postoperative due to oncological gastrectomy - Ribero, Gustavo; de Mello, Washington; Cartazzo, José M (Cirugía del Uruguay, 2000)
The authors present three cases of ischemic necrosis of gal/ bladder as a complication following gastrectomy and as an acute abdominal condition in a patient whose pathology, though basically vascular, had evo/ved.